ผลของแกนสับปะรดในผลิตภัณฑ์ปลาร้าถั่วเหลืองต่อการเจริญเติบโตของจุลินทรีย์ และคุณลักษณะทางประสาทสัมผัส (EFFECT OF PINEAPPLE CORES IN AN IMITATED FERMENTED FISH (PLA-RA) PRODUCTS MADE BY SOYBEAN ON THE GROWTH OF MICROORGANISMS AND SENSORY ATTRIBUTES) - ทูลธรรม นิจฉรา; บัวเนี่ยว ชัยวุฒิ; นามโยธา เฉลิมพร; ตาพั้ว จันทิมา; มะลิกรรณ์ บุบผา; แสงระพี พรปวีณ์ (Srinakharinwirot University Journal of Sciences and Technology, 2020)
The purpose of this study was to formulate the imitated fermented fish (Pla-ra) made by soybean and pineapple cores. Effects of addition of pineapple cores with different contents (2.91, 5.66 and 8.26% w/w) on changes of microorganisms and sensory attributes during the fermentation process were studied. 2,2-diphenyl-1-picrylhydrazyl (DPPH) antioxidant capacity and consumer acceptances (n=50) of the finished products were studied. Principal Component Analysis (PCA) was applied to observe relationships among the microorganisms, sensory attributes, 2,2-diphenyl-1-picrylhydrazyl (DPPH) antioxidant capacity and consumer acceptances of the finished imitated fermented fish products. The results were found that the product with 8.26% of pineapple cores had the optimum pH for the fermentation process on day 2 with a pH of 5.56 and ended on day 7 with a pH level of 5.04. The product had the lowest number of molds and yeasts (3.00 x106 CFU/Kg) and the highest number of lactic acid bacteria (4.75 x103 CFU/Kg) when compared to other products (P0.05). Also, the product with 8.26% of pineapple cores had the highest 2,2-diphenyl-1-picrylhydrazyl (DPPH) antioxidant capacity (P0.05) with IC50 of 1.28 x105 mM ascorbic acid equivalent. Its feature sensory attribute was a fermented odor, sour odor, roasted rice and umami taste. Moreover, this product obtained acceptance scores with the rather like level of all attributes (6.23-6.89). In conclusion, the addition of pineapple cores 8.26% accelerate the fermentation of imitated fermented fish product made by soybean and also enhance the health benefits of the product.